Is religion essential to education? In the 240th anniversary of birth of Friedrich Schleiermacher - Stępkowski, Dariusz (Paedagogia Christiana, 2008)
Friedrich Schleiermacher (1768–1834) is, after Luther and Calvin, the most significant protestant theologian, and a forerunner of philosophical hermeneutics. He is lesser known as a pedagogue, especially in Poland. The two hundred and fortieth birth anniversary of the author of Grundzüge der Erziehungskunst is an occasion to shed more light onboth the person and the work. The article is made up of two parts. The first one consists of an abridged biography of the Breslau-born thinker. According to Kurt Nowak, a contemporary investigator of Schleiermacher’s works, it is not possible to fully understand the thinker’s views without knowing his life. The second part aims to distill the main lines of thought to be found in the protestant pedagogue’s theory of education. Referring to On Religion (Über Religion) and Monologues (Monologen), the author of the article states that the foundation of Schleiermacher’s conception is the peculiar bond linking man with reality and himself. It consists of two moments: 1. (receptive) vision of the universe (Anschauung des Universums) and 2. (active) sense of boundlessness (Gefühl des Unendlichen). In Schleiermacher’s interpretations, this dual relationship is sometimes religion (or rather: a religious experience, religiosity), and sometimes education. In effect, religion and education become identical in his eyes. Yet this can be solely applied to the experiencing of sense of the primary dependence (ein schlechhinniges Abhängigkeitsgefühl). Any intention of its verbalization leads to the splitting of the self into subject and object. Because of this, thinking is brought to an entirely new level; it is the otherwise known controversy of religious upbringing versus public education.